Hospital-based Survey on Knowledge and Attitude toward Colorectal Cancer Screening among Indonesian Population - Murdani Abdullah; Achmad Fauzi; Ari Fahrial Syam; Dadang Makmun; Marcellus Simadibrata; Chudahman Manan; Joseph JY Sung; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: Several western countries have recommended colorectal cancer (CRC) screening, however the yield of CRC screening is still low. The acceptability of CRC screening is influenced by people’s knowledge and attitude. This study was conducted to evaluate the knowledge and attitude of Indonesian people toward CRC screening. Method: Adult Indonesian population aged 19–65 years was recruited in this hospital-based survey. Knowledge and attitude toward CRC screening were assessed by using structured questionnaires consisting of nine chapters. Result: There were 614 respondents recruited in this study. Most respondents (36.2%) incorrectly pointed out abdominal pain or pain around anus as the symptom of bowel cancer. Regarding CRC risk factors, eating fruits or vegetables rarely was the most frequent answer (28.5%) encountered. Only one-third (28%) of respondents mentioned colonoscopy as the Method for CRC screening. There were 38.1% of respondents who believed that CRC screening test might be harmful to the body. Up to 70.8% of the respondents agreed and strongly agreed that CRC screening test might cause physical discomfort. Two fifth (41.5%) of respondents believed that CRC screening test was embarrassing. More than half (58.8%) of respondents were afraid of having the CRC screening test. The test was too expensive according to 79.5% of respondents. Conclusion: The knowledge on CRC symptoms, risk factors, and screening tests is still low among Indonesian population. Our study result indicates that the lack of knowledge and the discouraging attitude among Indonesian population will be the major barriers to implement CRC screening in Indonesia.   Keywords: colorectal cancer, screening, knowledge, attitude